La inteligencia emocional - Goleman, Daniel (México, D.F. : Suma de Letras, 2001)
Presents information on how much influence a person's "emotional intelligence" has on their ability to succeed in their personal life and their career.
Adult
Text in Spanish.
Translation of: Emotional intelligence.
Includes bibliographical references and index.
Adult
Keywords: Emotions; Emotions and cognition; Emotions -- Social aspects; Emotions; Theory of knowledge; Spanish language; Emotions -- Social aspects